Recent Bibliography on Coroplastic Topics: 2016–2017 (Les Carnets de l’ACoSt)
This list of recent publications pertaining to coroplast studies has been compiled mainly from Dyabola. ACoSt welcomes notices of publications pertaining to coroplastic topics that focus on material from the Near East, Egypt, Old Europe, Africa, and the Americas, among other geographic areas. Please send notices to secretary@acost-membership.org.